2013
DOI: 10.1002/ajh.23457
|View full text |Cite
|
Sign up to set email alerts
|

Genetic modifiers of sickle cell anemia in the BABY HUG cohort: influence on laboratory and clinical phenotypes

Abstract: The recently completed BABY HUG trial investigated the safety and efficacy of hydroxyurea in infants with sickle cell anemia (SCA). To investigate the effects of known genetic modifiers, genomic DNA on 190 randomized subjects were analyzed for alpha thalassemia, beta‐globin haplotype, polymorphisms affecting endogenous fetal hemoglobin (HbF) levels (XmnI, BCL11A, and HBS1L‐MYB), UGT1A1 promoter polymorphisms, and the common G6PD A− mutation. At study entry, infants with alpha thalassemia trait had significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
47
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 44 publications
8
47
3
1
Order By: Relevance
“…The magnitude of these changes was not significantly correlated with the quantum of improvement of the evaluated clinical outcome parameters thereby suggesting the role of other factors. The results confirm that the effects of HU therapy in SCD override the influence of genetic modifiers as observed by Sheehan et al [13].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The magnitude of these changes was not significantly correlated with the quantum of improvement of the evaluated clinical outcome parameters thereby suggesting the role of other factors. The results confirm that the effects of HU therapy in SCD override the influence of genetic modifiers as observed by Sheehan et al [13].…”
Section: Discussionsupporting
confidence: 91%
“…A study in India did not find any significant influence of a-thal on clinical scores in SCD patients treated with HU [24]. These observational [13].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Some authors have hypothesized that the effect of HU on HbF level could act through HbF- promoting loci like BCL11A [26]. A recent GWAS studies have revealed further sequence variants that could influence the response to HU [27]. However, the precise molecular mode of action of HU, though these genetic variants, remained to be comprehensively determined.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Alpha-thalassemia (a-thalassemia) is present in about one-third of SCA patients and is associated with reduced hemolysis 7 and protection from albuminuria. 8 A polymorphism in BCL11A (rs1427407, minor allele frequency 0.25) leads to higher fetal hemoglobin (HbF) levels, 9 reduced hemolysis, 10 and amelioration of SCA-related complications, 11 although its relationship with sickle cell nephropathy is unknown.…”
mentioning
confidence: 99%